A method for preparing hollow carbon nanofibers using uniaxial electrospinning technology and its application
Hollow carbon nanofibers are prepared by uniaxial electrospinning technology, and hollow structures are formed in the process of high-temperature carbonization using polyacrylonitrile and cellulose acetate, which solves the problems of complex material preparation and insufficient electrochemical performance in the prior art, and achieves the preparation of hollow carbon nanofiber materials with high specific surface area and excellent electrochemical performance.
Patent Information
- Application Number
- CN202310210405.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-07
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-03-07
AI Technical Summary
The existing hollow carbon nanofiber materials have complex preparation processes and high equipment requirements, which are not suitable for large-scale industrial production. The challenge of improving specific capacity while maintaining flexibility is great.
Hollow carbon nanofibers are prepared by uniaxial electrospinning technology, and hollow structures are formed during high-temperature carbonization through polyacrylonitrile and cellulose acetate, thereby improving the specific surface area and porosity.
It realizes the controllable preparation of hollow carbon nanofibers, maintains the mechanical stability of the material, and improves the electrochemical performance and specific capacity, and is suitable for self-supported flexible supercapacitors.
Smart Images

Figure CN116219584B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrode materials, and more specifically to a method for preparing hollow carbon nanofibers by utilizing uniaxial electrostatic spinning technology and its application. Background Art
[0002] In recent years, with the rapid development of flexible portable electronic technology, flexible energy storage devices have become a research hotspot in recent years. Supercapacitors are considered to be outstanding next-generation flexible electronic energy storage devices due to their excellent charge and discharge rates, highest power density, and long cycle life. The development of flexible and wearable supercapacitors requires a series of conditions, including mechanical properties, bending properties, electrochemical properties at different bending strengths, and cycle stability. However, excellent electrochemical performance and superior flexibility are always difficult to achieve at the same time.
[0003] At present, carbon nanofibers (CNFs) obtained by electrospinning have a unique one-dimensional (1D) nanostructure, and the 3D network structure of ultra-long fibers interwoven with each other makes it easier to assemble into flexible devices. However, the lower capacitance of CNFs limits its further application. In order to increase the specific surface area of electrospun carbon nanofibers, researchers use KOH, CO2 and steam to physically and chemically activate them.
[0004] However, the porous structure obtained by activation greatly reduces the mechanical properties of the material, and the trade-off between the high surface area and mechanical flexibility during the activation process makes it unsuitable for application. How to improve the specific capacity of CNFs while maintaining its flexibility is one of the great challenges faced by researchers.
[0005] Hollow carbon nanofibers (HCNFs) have attracted extensive attention from researchers because they can increase the specific surface area and porosity of the material while maintaining good mechanical stability. However, the existing preparation processes of hollow carbon nanofiber materials mainly focus on coaxial electrospinning technology or hard film board methods. These preparation methods are complex, require high equipment, and are not conducive to large-scale industrial production.
[0006] Therefore, how to provide a method for preparing hollow carbon nanofibers using uniaxial electrospinning technology, increase the specific surface area and porosity of the material through uniaxial electrospinning technology and the synergistic effect between raw materials while maintaining good mechanical stability of the fiber, and achieve controllable preparation of HCNFs is a problem that technicians in this field urgently need to solve. Summary of the invention
[0007] In view of this, the purpose of the present invention is to provide a method and application of preparing hollow carbon nanofibers using uniaxial electrospinning technology. The method obtains nanoscale fibers by uniaxial electrospinning technology, and then forms hollow carbon nanofibers by utilizing the difference in shrinkage rates of polyacrylonitrile and cellulose acetate under high temperature environment during the carbonization process. The hollow structure increases the specific surface area of the carbon nanofibers and shortens the diffusion distance of ions, thereby improving the electrochemical properties of the flexible carbon nanofiber materials.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] A method for preparing hollow carbon nanofibers using uniaxial electrospinning technology comprises the following steps:
[0010] 1) preparing a polyacrylonitrile / cellulose acetate spinning precursor solution: adding polyacrylonitrile and cellulose acetate into an N,N-dimethylformamide solution and stirring evenly;
[0011] 2) Electrospinning: placing the precursor solution prepared in step 1) in a syringe pump and spinning it through a uniaxial electrospinning process to obtain sample A;
[0012] 3) Vacuum drying: placing the sample A prepared in step 2) in a vacuum oven for drying to obtain sample B;
[0013] 4) High-temperature carbonization: The sample B prepared in step 3) is pre-oxidized in an air atmosphere, and then a protective gas is introduced for high-temperature carbonization, and then cooled to room temperature to obtain hollow-structured carbon nanofibers.
[0014] The beneficial effects of the above scheme are as follows: utilizing the phase separation between polyacrylonitrile and cellulose acetate, obtaining one-dimensional nanofibers through uniaxial electrospinning technology, and then fixing the carbon skeleton of the fiber through pre-oxidation so that the fiber will not be crushed during high-temperature calcination. Finally, during the high-temperature carbonization process, utilizing the different shrinkage rates of polyacrylonitrile and cellulose acetate in a high-temperature environment, a hollow-structured carbon nanofiber is formed, wherein the hollow structure further increases the specific surface area of the material, shortens the ion diffusion distance, and improves the electrochemical properties of the carbon material.
[0015] Furthermore, in step 1), the mass ratio of polyacrylonitrile to cellulose acetate is (1-4): (1-4); the concentration of the N,N-dimethylformamide solution is 0.5 mol·L -1 ; The concentration of polyacrylonitrile in the precursor solution is 0.04 to 0.2 g·mL -1 .
[0016] Preferably, the mass ratio of polyacrylonitrile to cellulose acetate in step 1) is 1:1; the optimal concentration of polyacrylonitrile in the precursor solution is 0.07 g·mL-1 .
[0017] Furthermore, the stirring method in step 1) is magnetic stirring, the stirring time is 12 hours, and the stirring temperature is 25°C.
[0018] The beneficial effects achieved by the above preferred scheme are: through the preferred optimal ratio of polyacrylonitrile and cellulose acetate, the obtained hollow carbon nanofiber structure is more uniform, the specific surface area is larger, and the electrochemical performance is optimal.
[0019] Furthermore, in step 2), the positive electrode voltage of the uniaxial electrospinning is 8 to 20 kV, and the negative electrode voltage is -1 to -8 kV; the nozzle of the injection pump is 15 to 25 cm away from the receiving plate, and the solution flow rate is 4 μL·min -1 ~20μL·min -1 .
[0020] Preferably, the positive electrode voltage of the uniaxial electrospinning in step 2) is 10 kV, and the negative electrode voltage is -2.5 kV; the nozzle of the injection pump is 18 cm away from the receiving plate, and the solution flow rate is 8 μL·min -1 .
[0021] The beneficial effects achieved by the above preferred solution are: the needle spinneret diverges in a conical shape, falls on the receiving plate evenly and continuously, and there is no liquid accumulation, and the spinning effect is optimal.
[0022] Furthermore, in step 3), the vacuum oven drying temperature is 40-80° C., the drying time is 6-20 h, and the vacuum degree is 0.05 MPa.
[0023] Preferably, in step 3), the vacuum oven drying temperature is 60° C. and the drying time is 12 h.
[0024] Furthermore, the pre-oxidation heating rate in step 4) is 1 to 10°C min -1 The pre-oxidation temperature is 200-300°C and the holding time is 1-3h.
[0025] Preferably, the pre-oxidation heating rate in step 4) is 1°C·min -1 , the pre-oxidation temperature is 240℃ and the holding time is 1h.
[0026] Furthermore, the protective gas is nitrogen; the heating rate of the high temperature carbonization is 1 to 10°C·min -1 , the carbonization temperature is 700-1000℃, and the insulation time is 1-3h.
[0027] Preferably, the heating rate of the high temperature carbonization is 5°C·min -1 , the carbonization temperature is 800℃ and the holding time is 1h.
[0028] The beneficial effects achieved by the above preferred scheme are: the hollow carbon nanofibers prepared by the above method have good conductive network, good conductivity, uniform hollow structure, simple preparation and excellent electrochemical performance.
[0029] On the other hand, the present invention also provides a carbon nanofiber material with a hollow structure, and its application as a self-supporting flexible supercapacitor electrode material.
[0030] The technical effect achieved by the above technical solution is: applying the hollow carbon nanofibers prepared by the above method to the electrodes of self-supporting flexible supercapacitors can significantly improve the capacitance performance of the capacitor.
[0031] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0032] (1) The present invention adopts uniaxial electrospinning technology and utilizes the difference in shrinkage rate between polyacrylonitrile and cellulose acetate during high-temperature carbonization to obtain hollow carbon nanofibers, which have the advantages of high specific surface area, good electrical conductivity, rich pore structure, and simple preparation method.
[0033] (2) The hollow carbon nanofibers prepared in the present invention have good conductive networks, ion transport channels and flexibility, and can be applied to self-supporting flexible energy storage devices.
[0034] (3) The hollow carbon nanofiber material prepared by the present invention is used as an electrode material for a self-supporting supercapacitor and has a high specific capacity and excellent rate characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0036] Figure 1 This is an optical photograph of the hollow structure carbon nanofiber prepared in Example 1 of the present invention.
[0037] Figure 2 This is a scanning electron microscope photograph of the hollow structure carbon nanofiber prepared in Example 1 of the present invention.
[0038] Figure 3 This is a transmission electron microscope photograph of the hollow structure carbon nanofiber prepared in Example 1 of the present invention.
[0039] Figure 4The graphs are nitrogen adsorption-desorption curves of the hollow carbon nanofibers prepared in Examples 1-5 of the present invention and the solid carbon nanofibers prepared in the comparative example.
[0040] Figure 5 This is the X-ray diffraction spectrum of the hollow structure carbon nanofiber prepared in Example 1 of the present invention.
[0041] Figure 6 The cyclic voltammetry curves at different scan rates of Example 1 of the present invention are shown.
[0042] Figure 7 The constant current charge and discharge curves at different current densities of Example 1 of the present invention are shown.
[0043] Figure 8 It is a comparison chart of the specific capacity of Examples 1-5 of the present invention and the comparative example at different current densities. DETAILED DESCRIPTION
[0044] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] Example 1
[0046] A method for preparing hollow carbon nanofibers using uniaxial electrospinning technology specifically comprises the following steps:
[0047] (1) Weigh 0.7 g of polyacrylonitrile and 0.7 g of cellulose acetate in a mass ratio of 1:1, place in 10 mL of N,N-dimethylformamide solution, and stir magnetically at room temperature (25°C) for 12 h to fully dissolve.
[0048] (2) Set the positive voltage to 10KV and the negative voltage to -2.5KV, the distance between the syringe nozzle and the receiving plate to 18cm, and the solution flow rate to 8μL·min -1 , sample A was obtained by spun through uniaxial electrospinning process.
[0049] (3) Sample A prepared in step 2) is placed in a vacuum oven for drying to obtain sample B. The vacuum oven drying temperature is 60° C., the drying time is 12 h, and the vacuum degree is 0.05 MPa.
[0050] (4) The sample B prepared in step 3) was placed in a tube furnace for high-temperature carbonization treatment at 1°C min in an air atmosphere. -1The temperature was raised to 240°C at a rate of 1°C / min and the holding time was 1h. Then nitrogen was introduced for high-temperature carbonization at a heating rate of 5°C / min. -1 The carbonization temperature is 800°C, the holding time is 1 hour, and the hollow structured carbon nanofibers are obtained by cooling to room temperature.
[0051] The morphology and electrochemical performance of the hollow carbon nanofibers obtained in Example 1 were characterized:
[0052] Bending the hollow carbon nanofiber material shows that it has good flexibility, see Figure 1 .
[0053] The hollow carbon nanofiber material was scanned by electron microscope to obtain SEM photos, see Figure 2 .
[0054] The microstructure of the hollow carbon nanofiber material was analyzed and a transmission electron microscope image was obtained, see Figure 3 .
[0055] X-ray diffraction test of hollow carbon nanofiber materials, see Figure 5 .
[0056] The hollow carbon nanofiber material was electrochemically tested in a three-electrode system with the prepared material as the working electrode, platinum as the counter electrode, and mercury / mercuric oxide as the reference electrode. -1 The potassium hydroxide was used as the electrolyte and the test was carried out in the voltage range of -1 to 0 V. The cyclic voltammetry curves at different scan rates and the constant current charge-discharge curves at different current densities are shown in Figure 6 and Figure 7 .
[0057] Example 2
[0058] Compared with Example 1, the molecular weight of the polyacrylonitrile weighed in step (1) is 0.4 g, and the weight of the cellulose acetate is 1 g. The rest is the same as Example 1.
[0059] Example 3
[0060] Compared with Example 1, the weight of the polyacrylonitrile polymer weighed in step (1) is 1 g, and the weight of the cellulose acetate is 0.4 g. The rest is the same as Example 1.
[0061] Example 4
[0062] Compared with Example 1, the carbonization temperature in step (6) is 700°C, and the rest is the same as Example 1.
[0063] Example 5
[0064] Compared with Example 1, the carbonization temperature in step (6) is 900°C, and the rest is the same as Example 1.
[0065] Comparative Example
[0066] Compared with Example 1, the mass of the polyacrylonitrile polymer weighed in step (1) is 1.4 g, the mass of the cellulose acetate is 0 g, and the rest is the same as Example 1, thus obtaining solid carbon nanofibers.
[0067] The carbon nanofibers prepared in the comparative example and Examples 1-5 were tested using a nitrogen adsorption pore size analyzer. In a liquid nitrogen environment, the adsorption amount and adsorption-desorption isotherms at each partial pressure point were measured by injecting and pumping gas into the sample tube. Figure 4 .
[0068] The electrochemical performance of the carbon nanofibers prepared in the comparative example and Examples 1-5 was tested and calculated to obtain a comparison chart of the specific capacity of the solid carbon nanofibers and the hollow carbon nanofibers at different current densities, see Figure 8 .
[0069] The results show that compared with the carbon nanofibers prepared in the comparative example, the present invention uses the uniaxial electrospinning technology to construct a carbon nanofiber with a hollow structure based on the phase separation and carbon yield between the two polymers. The hollow structure increases the specific surface area of the carbon nanofiber and shortens the diffusion distance of ions. Based on these characteristics, Example 1 exhibits better electrochemical performance than the comparative example.
[0070] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0071] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing hollow carbon nanofibers using uniaxial electrospinning technology, characterized in that: The steps include: 1) preparing a polyacrylonitrile / cellulose acetate spinning precursor solution: adding polyacrylonitrile and cellulose acetate into an N,N-dimethylformamide solution and stirring evenly; 2) Electrospinning: placing the precursor solution prepared in step 1) in a syringe pump and spinning it through a uniaxial electrospinning process to obtain sample A; 3) Vacuum drying: placing the sample A prepared in step 2) in a vacuum oven for drying to obtain sample B; 4) High-temperature carbonization: The sample B prepared in step 3) is pre-oxidized in an air atmosphere, and then a protective gas is introduced for high-temperature carbonization, and then cooled to room temperature to obtain hollow carbon nanofibers; The mass ratio of polyacrylonitrile to cellulose acetate in step 1) is 1:1; the concentration of the N,N-dimethylformamide solution is 0.5 mol·L -1 ; The concentration of polyacrylonitrile in the precursor solution is 0.07 g·mL -1 ; The stirring method in step 1) is magnetic stirring, the stirring time is 12 hours, and the stirring temperature is 25° C.; The positive electrode voltage of the uniaxial electrospinning in step 2) is 10 kV, and the negative electrode voltage is -2.5 kV; the nozzle of the injection pump is 18 cm away from the receiving plate, and the solution flow rate is 8 μL·min -1 ; In step 3), the vacuum oven drying temperature is 40-80°C, the drying time is 6-20h, and the vacuum degree is 0.05Mpa; The heating rate of the pre-oxidation in step 4) is 1°C min -1 The pre-oxidation temperature is 240°C, the holding time is 1h; the protective gas is nitrogen; the heating rate of the high temperature carbonization is 5°C·min -1 , the carbonization temperature is 800℃ and the holding time is 1h.
2. A hollow structure carbon nanofiber, characterized in that: Prepared by the method of claim 1.
3. Application of the hollow structure carbon nanofiber according to claim 2 in self-supporting flexible electrode materials and wearable energy storage devices.
Citation Information
Patent Citations
Preparation method of composite carbon nanofibers with high specific surface area
CN105506784A
Porous carbon nano fiber material for adsorbing carbon dioxide and preparation method thereof
CN107051382A